Extraction of Antioxidants and Phenolic Contents from Purslane (Portulaca Oleracea L.) using Ultrasound Assisted Extraction with Maceration - Abu Hassan Shaari, Nur Aqilah; Che Pa, Nasrul Fikry (Progress in Engineering Application and Technology, 2023)
Purslane, or Portulaca oleracea L., is an edible weed that is a rich source of natural antioxidants. Recently, dietary supplements and skincare products made from natural ingredients are in demand. Conventional extraction techniques have disadvantages, including their low extraction rate, high energy usage, and high solvent consumption. Thus, the effectiveness of the combination extraction method, ultrasound-assisted extraction with maceration was explored. The antioxidant activity and the total phenolic content of Portulaca oleracea L. extracts were analyzed by the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay and Folin-Ciocalteu reagent method (FCR), respectively. The results showed that pulsed ultrasound assisted extraction at early part of the 24-hour maceration with 5 minutes, 100 W sonication was the most efficient compared to other techniques. Among the extraction methods of purslane extracts, 48-hour maceration without ultrasound displayed the highest total phenolic content (19.24 ± 1.01 mg GAE/g), whereas 72-hour maceration without ultrasound had the lowest with 14.30 ± 1.01 mg GAE/g. For purslane extracts, most of the samples give an inhibition percentage of 20 μg/mL, which ranges from 3.49 % to 58.70 %. Therefore, further research is recommended to explore alternatives to the current extraction method and evaluate the yield and efficiency of various extraction methods.